2019
DOI: 10.20944/preprints201909.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Additional Value of Using Satellite-Based Soil Moisture and Two Sources of Groundwater Data for Hydrological Model Calibration

Abstract: Although the complexity of physically based models continues to increase, they still need to be calibrated. In recent years, there has been an increasing interest in using new satellite technologies and products with high resolution in model evaluations and decision-making. The aim of this study is to investigate the value of different remote sensing products and groundwater level measurements in the temporal calibration of a well-known hydrologic model i.e. HBV. This has been rarely done for conceptual models… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Previous studies used ground‐based or alternatively remote sensing products or their combination as such additional information on hydrologic processes. Soil moisture (Kundu et al, 2017; Kunnath‐Poovakka et al, 2016; Parajka et al, 2006; Rajib et al, 2016; Shahrban et al, 2018), evapotranspiration (Gui et al, 2019; Herman et al, 2018; Immerzeel & Droogers, 2008; Kunnath‐Poovakka et al, 2016), and groundwater level data (Demirel et al, 2019; Seibert, 2000) were often used for model calibration to improve the model's internal consistency. These studies showed the added value of different observations besides runoff, for example, for soil moisture, evapotranspiration, and groundwater levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used ground‐based or alternatively remote sensing products or their combination as such additional information on hydrologic processes. Soil moisture (Kundu et al, 2017; Kunnath‐Poovakka et al, 2016; Parajka et al, 2006; Rajib et al, 2016; Shahrban et al, 2018), evapotranspiration (Gui et al, 2019; Herman et al, 2018; Immerzeel & Droogers, 2008; Kunnath‐Poovakka et al, 2016), and groundwater level data (Demirel et al, 2019; Seibert, 2000) were often used for model calibration to improve the model's internal consistency. These studies showed the added value of different observations besides runoff, for example, for soil moisture, evapotranspiration, and groundwater levels.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the isoWATFLOOD model (Stadnyk et al, 2013;Stadnyk and Holmes, 2020) is calibrated using both streamflow and isotopic -δ 18 O -data, but a visual -and thus rather subjective -evaluation of calibration by the modeller is necessary; Jian et al (2017) used, in a catchment where only a few streamflow measurements were available, river level data, and added three new parameters to a hydrological model to simulate the rating curve. Whereas infield measurements are not always common, satellite data are broadly available around the world, and numerous studies have used them in hydrological models: Immerzeel and Droogers (2008) used satellite evaporation to calibrate the SWAT distributed model through a composite criterion and got a better representation of the actual evaporation and less equifinality in parameter determination; Mostafaie et al (2018) performed a multi-objective calibration using NSE for streamflow and total water storage from GRACE satellite data; Milzow et al (2011) combined several satellite datasets -surface soil moisture, radar altimetry and total water storage -to calibrate a semi-distributed model in a catchment with few streamflow measurements through a composite of nine criteria; Demirel et al (2019) explored the use of dif-ferent combinations of objective functions, computed based on several satellite products measuring soil moisture and water storage, to calibrate a conceptual model, and achieved little gain in streamflow simulation performance; and Dembélé et al (2020) performed a composite calibration of a distributed model with four datasets -measured streamflow and satellite evaporation, soil moisture and water storage -and improved the model's representation of processes at the expense of a small degradation of the streamflow simulation performance.…”
Section: How Are Measured Data Used In Hydrological Modelling?mentioning
confidence: 99%